Adverse Reactions to BCG Vaccine and Maternal Home Care in Children Under 1 Year - Alarcón Velásquez, Lucia Nicole (2021)
Objective: To identify and describe the adverse reactions to the Bacillus Calmette - Guerin vaccine in children under 1 year of age and to identify and analyze maternal care at home against adverse reactions. Method: Qualitative research, with a case study approach. The participants were 15 mothers who take care of their children at the Toribia Castro Chirinos Health Center and 7 nurses who work in said establishment; The sampling was non-probabilistic, for convenience and the size was determined with the saturation and redundancy technique, the data were collected with the prior informed consent of the participants, with a semi-structured interview guide, validated by expert judgment and pilot test and processed through content analysis. The execution of the research was prior approval of the project by an Institutional Research Ethics Committee. Main Results: Two categories were obtained as results: I: Adverse reactions to the BCG vaccine. II: Maternal care against BCG vaccine reactions. General conclusion: The majority of mothers with children under 1 year of age who have been vaccinated with the BCG vaccine, state that they have observed the traditionally known reactions (nodule, pustule, ulcer and keloid scar), with certain peculiarities each and with a duration of time. varied in many cases different from literature, against which the nursing professional educates, being necessary that said professional, assess each case at the time of exercising their educational role in this matter.